Adult Attachment and Mindfulness on Mental Health: A Systematic Research Synthesis. (2019) - Jaurequi, Matthew E.
Abstract: Interest in the relationship between adult attachment and mindfulness has mushroomed over the past decade. Yet the associations between adult attachment and mindfulness related to mental health is less understood. This article provides a systematic research synthesis to elucidate the relationship between adult attachment, mindfulness, and mental health. Findings from 10 empirical articles identified that anxious and avoidant attachment and mindfulness together related to depression, anxiety, psychological functioning, and cortisol response. The effects of adult attachment and mindfulness on mental health is an exciting area for research and practice that can be advanced by the inclusion of key romantic relationship processes and partners within longitudinal or experimental study designs.